Healthcare in Asia: a perspective from primary care at the gateway to a continent - Jiwa, M.; Othman, S.A.; Hanafi, N.S.; Ng, C.J.; Khoo, E.M.; Chia, Y.C. (2012)
Malaysia has achieved reasonable health outcomes even though the country spends a modest amount of Gross Domestic Product on healthcare. However, the country is now experiencing a rising incidence of both infectious diseases and chronic lifestyle conditions that reflect growing wealth in a vibrant and successful economy. With an eye on an ageing population, reform of the health sector is a government priority. As in other many parts of the world, general practitioners are the first healthcare professional consulted by patients. The Malaysian health system is served by public and private care providers. The integration of the two sectors is a key target for reform. However, the future health of the nation will depend on leadership in the primary care sector. This leadership will need to be informed by research to integrate care providers, empower patients, bridge cultural gaps and ensure equitable access to scarce health resources